The Effect of Clinical Competence, Persona Image and Accessibility of Doctor's Services on Patient Revisit Intention at Hospital X - Fransiska Amelia Sugianto; Wiliam Santoso; Agoes Tinus Lis Indrianto (Journal Research of Social Science, Economics, and Management, 2025)
The purpose of this study is to analyze the relationship between the influence of clinical competence, persona image, and service accessibility on patient satisfaction, which will influence repeat visit intentions. This study employed a quantitative methodology, analyzing data collected from questionnaires completed by 182 respondents. Researchers carried out an analysis using primary data obtained by distributing questionnaires via Google Forms at Hospital X in the Solo Raya area. The research results showed that the doctor's clinical competence, persona image, and service accessibility influence patient satisfaction, which can influence the patient's intention to revisit. This research can provide important insights for health service providers, especially hospitals, to be able to develop strategies aimed at increasing patient retention through increasing clinical competence, positive persona image of doctors, and ease of service accessibility to improve service quality with the primary objective of enhancing the volume of patient visits.